Suppressive Regulation by MFG‐E8 of Latent Transforming Growth Factor β–Induced Fibrosis via Binding to αv Integrin: Significance in the Pathogenesis of Fibrosis in Systemic Sclerosis. Issue 2 (4th January 2019) - Fujiwara, Chisako; Uehara, Akihito; Sekiguchi, Akiko; Uchiyama, Akihiko; Yamazaki, Sahori; Ogino, Sachiko; Yokoyama, Yoko; Torii, Ryoko; Hosoi, Mari; Suto, Chiaki; Tsunekawa, Katsuhiko; Murakami, Masami; et al.
Abstract : Objective: Several studies have demonstrated that the secreted glycoprotein and integrin ligand milk fat globule–associated protein with epidermal growth factor– and factor VIII–like domains (MFG‐E8) negatively regulates fibrosis in the liver, lungs, and respiratory tract. However, the mechanisms and roles of MFG‐E8 in skin fibrosis in systemic sclerosis (SSc) have not been characterized. We undertook this study to elucidate the role of MFG‐E8 in skin fibrosis in SSc. Methods: We assessed expression of MFG‐E8 in the skin and serum in SSc patients. We examined the effect of recombinant MFG‐E8 (rMFG‐E8) on latent transforming growth factor β (TGFβ)–induced gene/protein expression in SSc fibroblasts. We examined the effects of deficiency or administration of MFG‐E8 on fibrosis mouse models. Results: We demonstrated that MFG‐E8 expression around dermal blood vessels and the serum MFG‐E8 level in SSc patients (n = 7 and n = 44, respectively) were lower than those in healthy individuals (n = 6 and n = 28, respectively). Treatment with rMFG‐E8 significantly inhibited latent TGFβ–induced expression of type I collagen, α‐smooth muscle actin, and CCN2 in SSc fibroblasts (n = 3–8), which suggested that MFG‐E8 inhibited activation of latent TGFβ as well as TGFβ signaling via binding to αv integrin. In a mouse model of bleomycin‐induced fibrosis (n = 5–8) and in a TSK mouse model (a genetic model of SSc) (n = 5–10), deficient expression of MFG‐E8 significantly enhanced both pulmonary and skin fibrosis, and administration of rMFG‐E8 significantly inhibited bleomycin‐induced dermal fibrosis. Conclusion: These results suggest that vasculopathy‐induced dysfunction of pericytes and endothelial cells, the main cells secreting MFG‐E8, may be associated with the decreased expression of MFG‐E8 in SSc and that the deficient inhibitory regulation of latent TGFβ–induced skin fibrosis by MFG‐E8 may be involved in the pathogenesis of SSc and may be a therapeutic target for fibrosis in SSc patients.